Development of Regional Economics Studies in Peru: Contributions and Criticisms - Palomino, Juan (2020)
This research presents an overview of the evolution of regional economic studies in Peru. After a brief introduction, the document presents a summary of the different conceptions of space in Regional Economics through time. In addition, the document shows the origins of Regional Economics, as well as the factors that explain the interest in the development of regional studies in the Latin American context. This document also explains the importance of the geographical space of Peru for regional research. Indeed, the country is the perfect setting because Peru has a wide geographic diversity (ecosystems, microclimates) throughout its territory, it has implemented a variety of public policies to propose economic growth measures, and it has many social issues to propose territorial policies (migration, crime, health, employment, among others). Despite these characteristics, regional research in Peru is relatively less than in other Latin  American countries. Finally, the document offers the contributions and criticisms of the regional studies in the Peruvian context.